Evaluasi Kariadi Information System pada Petugas Koding Rawat Jalan di RSUP dr. Kariadi Semarang - Nabilah Khoirun Nissa'; Feby Erawantini; Mochammad Choirur Roziqin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Based on a preliminary survey that I had done during the Field Work Practice at RSUP Dr. Kariadi Semarang.The output that was there produced the KIS system on the RME menu that was not yet in accordance with thewishes of the outpatient coding officer. In the KIS system, the SIMRS menu entry grouping encoding externalcauses or external causes only have 3 digits of 4 characters. The use of the KIS menu RME systemsometimes occurs errors that are not equipped with guidelines or guidelines if an error occurs. This studyaims to evaluate KIS (Kariadi Information System) users in outpatient coding officers. Use the methoddiscussed, namely the EUCS method to measure the level of satisfaction from using a system. The resultsthat have been obtained from this research in terms of the content (content) of the information obtained isquite helpful for coding officers. The lack of entry grouping coding on the external cause, if complete willbenefit the patient. In terms of accuracy (accuracy) still requires an accuracy process, for example, if the inputerror registers, the data that appears will be different and occasional errors also occur. In terms of format(display) the interface is quite attractive based on user needs. In terms of timeliness, the system is able toprovide up to date information. In terms of ease of use (ease of use) the system is easy to learn only the lackof guidance if there has been an error. This research resulted in several recommendations that IT staff officerscan receive input related to the constraints of the use of the coder officer system, the head of the medicalrecord conducts further evaluation and supervision of the use of the system.